2004
DOI: 10.1002/ejoc.200300434
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic Synthesis of Enantiomerically Pure (2S,3R,4S)‐4‐Hydroxyisoleucine, an Insulinotropic Amino Acid Isolated from Fenugreek Seeds

Abstract: A short six‐step synthesis of (2S,3R,4S)‐4‐hydroxyisoleucine (1a) with total control of stereochemistry is reported, the last step being the enzymatic resolution by hydrolysis of a N‐phenylacetyl lactone derivative using the commercially available penicillin acylase G immobilized on Eupergit C (E‐PAC). (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2004)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Several methods of chemo enzymatic synthesis of HIL have been reported. Wang Q. et al reported an eight-step synthesis process involving a stereoselective bioreduction step catalyzed by Geotrichum candidum (Wang et al 2002), and Rolland-Fulcrand V. et al reported a six-step synthesis process involving an enzymatic chiral resolution step catalyzed by immobilized penicillin acylase G (Rolland-Fulcrand et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Several methods of chemo enzymatic synthesis of HIL have been reported. Wang Q. et al reported an eight-step synthesis process involving a stereoselective bioreduction step catalyzed by Geotrichum candidum (Wang et al 2002), and Rolland-Fulcrand V. et al reported a six-step synthesis process involving an enzymatic chiral resolution step catalyzed by immobilized penicillin acylase G (Rolland-Fulcrand et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This decrease in rate may well be due to the increase in sterics in the proximity of the double bond; in the pseudoequatorial conformer (the more stable one), the methyl indeed hinders one face of the double bond, whereas the tosyl group hinders the other one (see Figure 3 for the structure of 4, which is closely related to 14). Finally, in a desire to explore the development of new compounds with antidiabetic properties and structurally related to 4-hydroxyisoleucine, [14] we envisaged the conversion of the protected amino alcohol 14 into the protected γ-hydroxy-α-amino acid 15 (Scheme 6). Thus, an oxidative www.eurjoc.orgcleavage of the terminal double bond of 14, followed by the esterification of the corresponding carboxylic acid, led to the protected γ-hydroxy-α-amino acid 15 in a (nonoptimized) yield of 50 %.…”
Section: Resultsmentioning
confidence: 99%
“…This ratio was deduced from a comparison of the integrals of the 1 H NMR resonances of 4-H (δ = 4.81 ppm, integral = 0.03 for cis-15; δ = 4.57 ppm, integral = 1.00 for trans -15). (Attempts to achieve purifi-NaHCO 3 (18), KCl (4.7), CaCl 2 (2.5), MgSO 4 ·7H 2 O (1.2), KH 2 PO 4 (1.2) and supplemented with 8.3 m glucose and 2 g/L bovine serum albumin. The pH of the medium was adjusted to 7.4 by bubbling through a mixture of O 2 /CO 2 (95:5).…”
Section: 6-dideoxy-3-o-methyl-d-xylo-hexono-14-lactone (8b)mentioning
confidence: 99%